Evaluation of haematological and coagulation profile in covid-19 patients: A prospective study (Panacea Journal of Medical Sciences, 2024)
Introsuction: Covid-19 stems from the new coronavirus, Severe acute respiratory syndrome coronavirus 2. Careful evaluation of laboratory indices at baseline and during the disease course can assist in identifying disease progression and prompt treatment. Present study is aimed to analyse these laboratory parameters of patients with Covid-19 infection. Our study seeks to examine the hematological and coagulation profile parameters in patients with confirmed positive results in RT-PCR testing for COVID-19 in ICU and non ICU wards. The study involves assessing hematological and coagulation profile parameters both upon admission and after a 4-day hospitalization period, with a subsequent analysis of their correlation with radiological findings.Materials and Methods: The approach employed in this investigation is that of a prospective observational study conducted over a period of 24 months on 300 patients. All RT-PCR positive Covid-19 patients above 18 years of age were included. 300 patients were divided into 2 groups A and B. Group A included patients diagnosed as RT-PCR positive Covid-19 and admitted in non-ICU ward. Group B included RT-PCR positive patients admitted in ICU. Haematological parameters like Complete blood count (CBC) and coagulation profile parameters like Prothrombin time (PT), Partial thromboplastin time (Aptt), Fibrinogen and D-dimer were studied on the day of admission and on 4th day of hospital stay. These laboratory parameters were correlated with radiological findings and patients outcome.Discussion: This study aims to give importance to the laboratory parameters at baseline and during the disease course so that patient’s clinical complications can be predicted early and appropriate management can be done.